LONG-TERM EFFECTS OF OLMESARTAN, AN ANG II RECEPTOR ANTAGONIST, ON BLOOD PRESSURE AND THE RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM IN HYPERTENSIVE PATIENTS - Shuichi Ichikawa; Yoshiaki Takayama (Российский кардиологический журнал)
The object of this study is to evaluate the long-term effects of olmesartan on hypertension and the renin-angiotensinaldosterone system in hypertensive patients. This study evaluated 26 hypertensive male and female outpatients, 38-69 years of age, with a systolic blood pressure ≥160 mm Hg and/or a diastolic blood pressure ≥95 mm Hg. Oral doses of 5 to 40 mg olmesartan were administered once daily. Blood pressure and renin-angiotensin-aldosterone parameters (plasma renin activity and plasma angiotensin I, II, and aldosterone concentrations) were evaluated at 12-16 weeks, 6 months, and 1 year after the start of olmesartan administration. Systolic and diastolic blood pressures were significantly decreased following the administration of olmesartan. The observed decreases in systolic and diastolic blood pressures after 1 year of treatment were 28,8±2,1 mm Hg and 15,8±1,3 mm Hg, respectively. No change was observed in the pulse rate. The plasma renin activity increased significantly from a baseline premedication mean of 1,26±0,31 ng/ml/h to a mean of 2,58±0,74 ng/ml/h and 2,87±0,72 ng/ml/h after 6 months and 1 year of treatment, respectively. Angiotensin II levels decreased significantly from a baseline of 20,4±3,2 pg/ml to a mean of 8,6±2,1 pg/ml and 6,8±1,8 pg/ml after 6 months and 1 year of treatment, respectively. The plasma aldosterone level also decreased significantly after 6 months of treatment. In hypertensive patients, the long-term administration of olmesartan, a novel AT, receptor antagonist, decreased both blood pressure and plasma angiotensin II levels.